Single-cell RNA-seq reveals functionally distinct biomaterial degradation-related macrophage populations. (October 2021) - Huang, Jiayun; Fan, Chunmei; Chen, Yangwu; Ye, Jinchun; Yang, Yuwei; Tang, Chenqi; Zhang, Hong; Fei, Yang; An, Chengrui; Xie, Yuanhao; Liu, Hua; Yin, Zi; et al.
Abstract: Macrophages play crucial roles in host tissue reaction to biomaterials upon implantation in vivo . However, the complexity of biomaterial degradation-related macrophage subpopulations that accumulate around the implanted biomaterials in situ is not fully understood. Here, using single cell RNA-seq, we analyze the transcriptome profiles of the various cell types around the scaffold to map the scaffold-induced reaction, in an unbiased approach. This enables mapping of all biomaterial degradation-associated cells at high resolution, revealing distinct subpopulations of tissue-resident macrophages as the major cellular sources of biomaterial degradation in situ . We also find that scaffold architecture can affect the mechanotransduction and catabolic activity of specific material degradation-related macrophage subpopulations in an Itgav-Mapk1-Stat3 dependent manner, eventually leading to differences in scaffold degradation rate in vivo . Our work dissects unanticipated aspects of the cellular and molecular basis of biomaterial degradation at the single-cell level, and provides a conceptual framework for developing functional tissue engineering scaffolds in future.